“Los costos de producción del banano tipo valery y su efecto en la rentabilidad de la Agrícola Bananera 6 Estrellas del cantón La Maná”. - Chusin Noroña, Wellington Johnny (2021)
The main purpose of the research work is to find solutions to the problem detected in this way: "the production costs of banana Valery and its effect on the profitability of the “6 stars” farm located in La Maná canton". In the present times this farm only accumulates the costs and does not administer them which does not put in evidence the activities that do not add value to the products or services, on the other hand at the moment of costing the products or service the indirect costs of the manufacture and the operational ones are not assigned of suitable form, this causes that the company does not have some real costs of the elaborated products or given services generating difficulties on having known the profitability that the same one generates. For this reason and based on the concerns that are reflected from the needs of the "6 Estrellas" farm regarding the costs incurred in the productions carried out, to establish the cost of production three processes were established, planting, crop maintenance and harvesting obtaining a production cost of $ 17,159.31 and a profit per box of bananas of $ 2.01 per box. The control of each process allows knowing the viability of the accounting processes in addition to knowing clearly which are the profitability ratios that the company presents in the accounting operations carried out.